Theoretical Study of Absorption of Light Due to Effect of Ponderomotive Force - Thakur, P. K.; Nakarmi, J. J. (Journal of Nepal Physical Society, 2019)
Absorption of light due to effect of ponder motive force in laser plasma interaction which has seen that the nonlinear interaction results from rigorous application of the ponder motive force description based on Lorentz’s theory. The deduced equation of motion is more general than that of the two–fluid model of the plasma and that used in the theory of microwave interaction with plasma. As might be expected, the forces are only in the direction of lower plasma densities and tangential forces vanish only with the general equation of two–fluid model. This result has been verified up to the third order in the spatial variation of the electron density. In addition it is seen that the collision frequency decreases continuously with the increase in temperature. From these results, it is concluded that the absorption coefficient decreases continuously with the increase in temperature. Furthermore, this work describes the variation of the absorption coefficient with laser light frequency and shows that the absorption coefficient depends on the frequency of light.